Kyrgyz Republic : Diagnostic Review of Consumer Protection and Financial Literacy, Volume 1. Key Findings and Recommendations - World Bank (Washington, DC, 2014)
The Diagnostic Review for Consumer Protection and Financial Literacy (CPFL) provides a detailed assessment of the institutional, legal and regulatory framework for consumer protection in two segments of the financial sector: banking and microfinance. The review was undertaken in response to a request for technical assistance in the field of financial consumer protection made by the National Bank of the Kyrgyz Republic (NBKR) in November 2012.